The Militant Listener: Reading Mongane Wally Serote’s Sikhahlel’ u-OR alongside Walter Benjamin’s Theses on the Philosophy of History - Ferguson, Retha (Kronos: Southern African Histories, 2022)
The Militant Listener: Reading Mongane Wally Serote’s Sikhahlel’ u-OR alongside Walter Benjamin’s Theses on the Philosophy of History In Sikhahlel’ u-OR: A Praise Poem for Oliver Tambo, Mongane Wally Serote presents an unflinching yet delicate meandering through the questions, reflections and provocations resistance history offers up through O. R. Tambo’s life. As Ciraj Rassool points out, in this work Tambo appears not as an individual, but as an integral node in a web connecting various lives. This counter-neoliberal interpretation of Tambo’s life offers what Michael Löwy calls ’a heterodox form of the narrative of emancipation’ rebuilding the struggle hero narrative along a decentred framework. By radically dislodging this narrative, Tambo is portrayed as the ’non-iconic icon’ he was esteemed to embody, and in this move, the poem, notably, points to the dearth of dialectic politics, both in our quotidian praxis, and the commemoration of others. Aptly, Serote’s work contributes to what Souleymane Bachir Diagne and Jean-Loup Amselle describe as a ’total decentring of all thought, one that rejects all "centrisms" and highlights instead branchings and connections, transfers, analogies and reciprocal influences between cultural places and intellectual fields that may be distant but are not distinct in space and time’. To this end, the poem presents us with a constellation of historical actors who flicker on the horizon, beckoning us to engage in the labour of freedom (’here we go again / the hour demands us to be daring once more / to emerge from a possible storm’).